Harm perceptions of nicotine‐containing products and associated sources of information in UK adults with and without mental ill health: A cross‐sectional survey. (17th September 2021) - Perman‐Howe, Parvati R.; Horton, Marie; Robson, Deborah; McDermott, Máirtín S.; McNeill, Ann; Brose, Leonie S.
Abstract: Background and Aims: People with mental ill health are more likely to smoke and experience smoking‐related harm than those without. Switching from combustible tobacco to lower‐risk nicotine‐containing products may be of benefit; however, misperceptions of harm may prevent their use. We aimed to assess, among adults with and without mental ill health, (1) perceptions of harm from nicotine and relative harm and addictiveness of different nicotine‐containing products and (2) sources of information associated with harm perceptions. Design: Cross‐sectional study. Setting and Participants: On‐line survey of adults ( n = 3400) who smoke cigarettes and/or use e‐cigarettes, or have recently stopped, in the United Kingdom. Measurements: Outcomes: harm perceptions of nicotine; relative perceived harm and addictiveness of different nicotine‐containing products; sources of information for harm perceptions of nicotine, cigarette smoking and e‐cigarettes. Demographics: sex, age, education, ethnic group and region. Other measures: self‐reported smoking, vaping and mental health status. Analyses: frequencies and logistic regressions adjusting for demographic/other measures. Findings: Among those with serious mental distress (versus no/low mental distress): 9.6% [13.9%, adjusted odds ratio (aOR) = 0.69, 95% confidence interval (CI) = 0.50–0.97] correctly identified that none/a very small amount of the health risks of smoking cigarettes come from nicotine; 41.7% (53.5%, aOR = 0.67, 95% CI = 0.54–0.84) perceived e‐cigarettes and 53.2% (70.3%, aOR = 0.62, 95% CI = 0.50–0.77) perceived nicotine replacement therapy to be less harmful than cigarettes; and 42.1% (51.3%, aOR = 0.77, 95% CI = 0.62–0.95) perceived e‐cigarettes as being less likely than cigarettes to cause cancer, 35.4% (45.5%, aOR = 0.71, 95% CI = 0.57–0.88) heart attacks and 34.9% (42.3%, aOR = 0.80, 95% CI = 0.64–0.99) lung problems. The most popular sources of information for cigarette smoking, e‐cigarettes and nicotine were scientific experts' opinions and media reports, with little variation by mental distress. Conclusions: Among adults with a history of tobacco and/or e‐cigarette use, those with serious mental distress appear to have less accurate harm perceptions of nicotine and nicotine‐containing products than those with no/low distress, despite reporting similar sources of information.